ANALISIS PERAN GURU DALAM MENGELOLA KELAS UNTUK PENGUATAN LINGKUNGAN BELAJAR YANG KONDUSIF - Dede Irma Agustiana; Suharjuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in managing the classroom to create a conducive learning environment through a literature review approach. The method used is a literature study by examining various relevant scientific journals, which are then analyzed using content analysis techniques. The results show that teachers have an important role as managers, facilitators, and motivators in creating a comfortable and effective learning atmosphere. Effective classroom management includes physical and psychological aspects, as well as the use of varied learning strategies. A conducive learning environment has a positive impact on students' motivation, participation, and learning outcomes.